Association study of single nucleotide polymorphisms in IL-10 and IL-17 genes with the severity of microbial keratitis. Issue 6 (December 2019) - Carnt, Nicole A.; Cipriani, Valentina; Stapleton, Fiona J.; Calder, Virginia; Willcox, Mark D.
Abstract: Purpose: Exploratory analysis to assess the association of single nucleotide polymorphisms (SNPs) in the interleukin (IL) 10 and IL-17 genes with severity of contact lens keratitis. Methods: This was a retrospective case control study of 88 contact lens keratitis cases (25 severe) and 185 healthy contact lens wearers recruited from studies conducted at Moorfields Eye Hospital and in Australia-wide during 2003–2005. Buccal swab samples were collected on Whatman FTA cards and mailed by post for DNA extraction and SNP genotyping. IL-10 (rs1800871; rs1800896; rs1800872) and IL-17 (rs1800871; rs1800896; rs1800872) SNPs were screened by pyrosequencing. Genetic association analyses were performed via Cochran-Armitage trend tests and logistic regression models using PLINK software. Results: None of the SNPs tested showed evidence of association with severity of contact lens keratitis at P  <  0.05. Nevertheless, minor allele G in SNP rs2397084 of the IL-17F gene was associated with increased risk of severe MK, with OR=2.1 (95% CI=0.9-4.8, P  = 0.066). Conclusion: Our study cannot exclude with confidence that genetic variation in the IL-17 F proinflammatory cytokine is associated with more severe outcomes of MK. However, there is general body of information that the IL-17 pathway is important in the mechanisms of MK. Studies with larger power and the expanded array of laboratory tools will elucidate the exact role of IL-17 in MK.